TEACHING WITH TECHNOLOGY: Integrating Information and Communication Technology (ICT) into Curriculum - Garg, Vineeta (Voices of Teachers and Teacher Educators, 2017)
This paper discusses the need to incorporate ICT into school curriculum to maximize educational outcomes. It highlights technology integration, challenges faced in implementing ICT and possible solutions.